Analysis for wave power capture capacity of two interconnected floats in regular waves. (November 2017) - Zheng, Siming; Zhang, Yongliang
Abstract: The most representative of raft-type wave energy converters (WECs) is one composed of two interconnected floats, which uses the relative rotation between the floats to drive a Power Take-Off (PTO) system, achieving power capture from ocean waves. This paper presents a fundamental investigation into the wave power capture capacity of two interconnected floats with arbitrary float length. Linear hydrodynamics of the interconnected floats and a linear PTO system are employed, which enables us to carry out a frequency-domain analysis. Analytical formulas are derived of an optimized PTO damping and PTO stiffness/inertia for maximizing wave energy conversion in regular waves with/without consideration of relative rotary motion constraints due to the restraints of pump stroke or/and collision problem between the floats. The analytical model is then employed to examine the influence of fore-and-aft float length ratio, PTO system and float rotary inertia radius on the power capture capability of the two interconnected floats. It is concluded that for general wave conditions and specified total float length, two interconnected floats with the fore one properly shorter than the aft one possess high capacity in power absorption. Highlights: Present an analytical model for PTO optimization of two interconnected floats. Explore the effect of float length ratio on power capture capability. Interconnected floats with inverse length ratio share the same optimal PTO damping. Proper rotary inertia radius of floats could further improve power capture capacity.